PROBLEMA FORMĂRII MATURITĂŢII ŞCOLARE ŞI A COMPORTAMENTELOR DE BAZĂ ÎN PREŞCOLARITATE - USM ADMIN (Moldova State University, 2008)
The present article deals with the implementation in practice of the new variant of the entire university education. In the approach of this reform it is needed: the solution of the problem of reorganization of the educational system in the kindergarten for innovation of the process of preparing of children for the life, and what is more important for school.